The Connotative Meaning of the Lyrics of Song Roman Picisan by Dewa 19 - Shiva Indira; Izzah (Raja Zulkarnain Education Foundation, 2025)
Connotative meaning is a branch of linguistics, specifically semantics, that is, the additional meaning attached to a word, group of words, or sentence beyond its original meaning. Connotative meaning is usually influenced by feelings, emotions, or culture. When someone uses a word with a connotative meaning, it means they want to convey something deeper, such as a positive or negative feeling, or a sarcasm. This research focuses on the analysis of semantic studies, namely the connotative meaning in the lyrics of the song Roman Picisan by Dewa 19. The lyrics of this song express feelings of longing and hope to be with a loved one, as well as depicting the struggle and honesty in undergoing the love relationship. The method used is qualitative analysis with data analysis techniques using the referential matching method proposed by Mahsun. Data collection was carried out through observation with listening, note-taking, and documentation techniques by writing down every word and sentence in the song lyrics. The analysis was carried out by identifying words or sentences that contain connotative meaning, then analyzing the data results according to the method used. Connotative meaning in this study is understood as an emotional, associative, and symbolic meaning that goes beyond lexical meaning, reflecting subjective experiences, social values, and cultural nuances inherent in linguistic expressions. The results show that the lyrics in the song contain many connotative meanings that not only function as artistic expressions, but also as a reflection of cultural dynamics and complex collective identities. These findings provide an important contribution in understanding the relationship between lyric literature and cultural contexts in Indonesian popular music.